First-Principle Insights into Positive Triboelectrification of Polyoxymethylene Through Homolytic Bond Rupture - Giulio Fatti; Hyunseok Ko; Sung Beom Cho (Nanoenergy Advances)
Understanding the mechanism underlying triboelectrification (TE) in polymers is crucial for developing cheap and effective triboelectric nanogenerators. Finding out how a polymer becomes tribopositive is especially relevant, as most polymers tend to charge negatively, reducing the power output and the range of applications. Thus far, it has remained unclear whether TE in polymers is to be attributed to homolytic ion transfer, heterolytic material transfer, or electronic transfer. Investigating the triboelectrification mechanism of polyoxymethylene by first-principle investigations, this study reveals a novel pathway driven by homolytic bond rupture. Our study demonstrates that the homolytic cleavage of a C–H bond upon contact with a metal surface drives a rearrangement in the oxidation state of the carbon atom, leading its dangling bond to cede an electron to the countersurface, leading to significant positive charging of the POM. This mechanism aligns with the triboelectric series and experimental observations. These insights suggest that TE mechanisms can be more complicated than heterolytic material transfer, depending on material-specific composition and chemistry. This study potentially paves the way for designing materials with tailored triboelectric properties for enhanced nanogenerator performance.